APPLICATION OF A RESISTIVITY SURVEY AND GEOGRAPHICAL INFORMATION SYSTEM (GIS) ANALYSIS FOR HYDROGEOLOGICAL ZONING OF A PIEDMONT AREA, HIMALAYAN FOOTHILL REGION, INDIA - Israil M.; Al-hadithi M.; Singhal D.C. (My University, 2006)
A Geographical Information System (GIS) has been used for the integration of the results of 70 vertical electrical soundings and hydrogeological data in the piedmont zone of the Himalayan foothills region of Uttaranchal, India. Indian remote sensing (IRS) LISS-III data has been used to prepare thematic maps for the geomorphology and slope maps of the area. The ranges of electrical resistivity values have been assigned to the different formations by calibrating electrical resistivity values with the borehole data. Electrical resistivity, groundwater level monitoring, and borehole and remote sensing data have been integrated in the GIS analysis to delineate the hydrogeological zoning in the study area. Suitable weights were assigned to the different features affecting the groundwater potential. The total score for a particular location is translated in terms of groundwater potential of the area. The results indicate that the southern part of the study area has a very good groundwater potential for meeting the demand of water for irrigation and domestic purposes whereas the steeply sloping area in the northern part, having high relief, has a poor groundwater potential. The resulting delineation of groundwater potential zones are in general agreement with the available yield data of the tube wells.
Keywords: PIEDMONT; HIMALAYAN FOOTHILL REGION; ELECTRICAL RESISTIVITY; GIS; GROUNDWATER RESOURCES